2018
DOI: 10.1200/jco.2017.76.5941
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analyses of the 21-Gene Assay in Breast Cancer: Systematic Review and Critical Appraisal

Abstract: Purpose Prior studies examining cost effectiveness of the 21-gene assay (Oncotype DX [ODX]) for women with hormone receptor-positive, early-stage breast cancer have yielded disparate results. We aimed to explore why these analyses may have yielded different conclusions. Methods We conducted a systematic literature review of cost-effectiveness analyses (CEAs) of ODX. We examined the extent to which the structure of CEA modeling, the assumptions of the models, and the selection of input parameters influenced cos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
70
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 52 publications
1
70
0
1
Order By: Relevance
“…45,46 To estimate prevalence or distributions of RS, population-based studies are preferable to randomized controlled trials (RCTs) because of the external validity consideration. 14 Based on our population-based study, only 3% of patients who were classified as low-risk patients (according to their PREDICT estimation) had RS≥31. Our results differed substantially from those of post hoc analyses of a subset of participants enrolled in an RCT 47 that found that approximately 15% of the low-risk group (based on AO estimation) had RS≥31 (supplemental eTable 8).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…45,46 To estimate prevalence or distributions of RS, population-based studies are preferable to randomized controlled trials (RCTs) because of the external validity consideration. 14 Based on our population-based study, only 3% of patients who were classified as low-risk patients (according to their PREDICT estimation) had RS≥31. Our results differed substantially from those of post hoc analyses of a subset of participants enrolled in an RCT 47 that found that approximately 15% of the low-risk group (based on AO estimation) had RS≥31 (supplemental eTable 8).…”
Section: Discussionmentioning
confidence: 86%
“…[8][9][10][11][12][13] However, several important methodologic limitations may have diminished the accuracy of previous cost-effectiveness analyses (CEAs). 14 First, these studies tended to combine all patients into a single group, [9][10][11] irrespective of their clinical and pathologic features. Such an approach, ignoring tumor characteristics when evaluating ODX, is not consistent with actual clinical practice because it assumes that all patients would be treated without consideration of their clinical characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] However, not all studies reported declines, and recent critical review of these analyses showed potential biases that may substantially influence study findings. 13 Previous work found a differential impact of RS testing on chemotherapy use, with significant reductions only among Medicare beneficiaries with high-risk disease. 15 For this reason, we hypothesized that the greatest cost reduction with RS testing would occur among younger, healthier patients with highrisk disease.…”
Section: Discussionmentioning
confidence: 97%
“…[4][5][6][7][8][9][10][11][12] However, these economic models require numerous assumptions and may be influenced substantially by investigator bias. 13 Furthermore, patients' treatment decisions can vary depending on personal preferences and priorities, and they may not follow test-based or physicianrecommended treatment. Contrary to guideline recommendations, some patients with low-risk disease receive RS testing 14 and have a higher likelihood of undergoing chemotherapy than those who do not receive testing.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] Generally, the 21-GA outperforms traditional clinicopathologic information, 18,19 but owing to its high cost, its unrestricted use could impose a substantial economic burden on society. Although several studies have concluded that the 21-GA is cost-effective, [20][21][22] a recent systematic literature review 23 questions their failure to consider a number of factors (eg, patients' clinicopathologic information) that are widely considered by oncologists before making chemotherapy decisions.…”
Section: Introductionmentioning
confidence: 99%